2020
DOI: 10.1002/humu.24139
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic TMEM251 variants in patients with severe skeletal dysplasia and extreme short stature

Abstract: Skeletal dysplasias are a heterogeneous group of disorders ranging from mild to lethal skeletal defects. We investigated two unrelated families with individuals presenting with a severe skeletal disorder. In family NMD02, affected individuals had a dysostosis multiplex-like skeletal dysplasia and severe short stature (<−8.5 SD). They manifested increasingly coarse facial features, protruding abdomens, and progressive skeletal changes, reminiscent of mucopolysaccharidosis. The patients gradually lost mobility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Using its endogenous antibody, we observed that both long and short isoforms of TMEM251 colocalized with the cis-Golgi marker GM130 (Supplementary Fig. 4a, b ), which is consistent with the previous report that TMEM251-GFP is localized to Golgi 10 . A small fraction of TMEM251 also colocalized with the early endosome marker EEA1 and the lysosome marker LAMP2 (Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Using its endogenous antibody, we observed that both long and short isoforms of TMEM251 colocalized with the cis-Golgi marker GM130 (Supplementary Fig. 4a, b ), which is consistent with the previous report that TMEM251-GFP is localized to Golgi 10 . A small fraction of TMEM251 also colocalized with the early endosome marker EEA1 and the lysosome marker LAMP2 (Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
“…Mechanistically, GCAF is essential for the processing and activity of GNPT. Symptomatically, individuals who carried the pathogenic GCAF mutation displayed severe symptoms reminiscent of MLII 10 . Therefore, we propose classifying this MLII-like inherited metabolic disorder as Mucolipidosis type V.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our estimated divergence times support the notion that hadal snail sh do have the ability to cross trenches, which is also consistent with recent studies on similarities in the composition of gut microbial taxa of two hadal snail sh species from the Kermadec and Mariana Trenches 51 . As a complement, the speci c loss of genes in hadal snail sh also suggests a possible ability to tolerate short-term starvation and achieve neutral buoyancy through lower skeletal density, all of which may further contribute to their ability to cross trenches 1,29,37,40,41 . In addition, a previous study suggested that hadal snail sh may develop in shallow waters during juvenile life and then descend to greater depths in adulthood 52 .…”
Section: Discussionmentioning
confidence: 99%
“…17). These two genes encode transmembrane proteins, and loss-of-function mutations have now been found that may affect bone mineral deposition and thus bone development and body growth 40,41 . Furthermore, many genes that determine chondrocyte differentiation and bone mineralization were found to be differentially expressed in the bones of hadal snail sh and Tanaka's snail sh.…”
Section: Reduced Bone Mineralizationmentioning
confidence: 99%